Assessment of Agricultural information needs in African, Caribbean & Pacific (ACP) States: Country Study: Swaziland - Phiri, Zilole M.K. (Technical Centre for Agricultural and Rural Cooperation, 2008)
This study commissioned by CTA aims to identify agricultural information needs of key actors / beneficiaries for CTA products and services, potential actors ..and, to develop some baseline data to facilitate subsequent monitoring activities.